2010
DOI: 10.1007/s10163-010-0292-y
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption characteristics of Cu2+ and Zn2+ from aqueous solution using carbonized food waste

Abstract: The aim of the present study was to analytically provide adsorption characteristics of Cu 2+ and Zn 2+ using carbonized food waste (CFW); more specifi cally, batch tests were conducted using various concentrations of metal ions, contact times, and initial pH levels in an attempt to understand the adsorption removal of heavy metal ions in aqueous solution at concentrations ranging between 50 and 800 mg/l. The results confi rmed that the adsorption equilibrium was established within a maximum of 80 min, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Matrix effects are the main problem in the atomic absorption spectrometry determination of metals in highly saline samples (31)(32)(33)(34)(35)(36)(37). The effect of some cations, anions, and some IA and IIA group metals on the recovery of the analytes was investigated using model solutions containing 20 µg lead and 10 µg cobalt and each foreign ion separately.…”
Section: Effect Of Foreign Ionsmentioning
confidence: 99%
“…Matrix effects are the main problem in the atomic absorption spectrometry determination of metals in highly saline samples (31)(32)(33)(34)(35)(36)(37). The effect of some cations, anions, and some IA and IIA group metals on the recovery of the analytes was investigated using model solutions containing 20 µg lead and 10 µg cobalt and each foreign ion separately.…”
Section: Effect Of Foreign Ionsmentioning
confidence: 99%
“…Li et al [14] showed that the greatest amount of energy was produced at 250 • C, although a change in carbon content was not significant through the characteristic food waste carbonization products using hydrothermal carbonization at 225 • C, 250 • C, and 275 • C. Parshetti [15] and Han et al [16] presented a possibility to treat contaminated water with carbonized food waste using the fact that char has an adsorption ability according to the carbonization temperature. Ahmed and Gupta [17] carried out the study regarding syngas, hydrogen gas, and energy recovery through food waste pyrolysis and gasification at the high temperature of 800~900 • C and Liu, Haili, et al [18] studied the effects of chloride salts contained in food waste on the production of bio-oil and gas through pyrolysis using microwave.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the removal of Zn(II) from wastewaters is important. Some methods are used to remove Zn(II) from wastewater, such as ion-exchange [1], precipitation [2], adsorption [3][4][5][6][7], membrane filtration [8] and solvent extraction [9,10]. Adsorption process is a simple and rapid method for removal of metal ions.…”
Section: Introductionmentioning
confidence: 99%